The atomization of a latex solution / Jaafar Omar and Saridun Ismail - Omar, Jaafar; Ismail, Saridun (1985)
Atomization is a relatively new technique and have a broad in the industries nowadays. It is a process of breaking up of fluid (feed) into droplets. The combination with ‘spray’ and 'dry' in the atomization field, made the atomization process become more competitive. The range of products suitable for atomization continue to expand. In this field, the range of droplets sizes produced by this process is between 20 to 500 microns. For the 'process of atomization is to be achieved, a suitable increase in specific surface area of the liquid via efficient contracting final separation of the phase must occur. The drop size distribution can be determine using a photography method.